Touching the Lived Body in Patients with Medically Unexplained Symptoms. How an Integration of Hands-on Bodywork and Body Awareness in Psychotherapy may Help People with Alexithymia - Calsius, Joeri; De Bie, Jozef; Hertogen, Raf; Meesen, Raf (Frontiers in Psychology, 2016)
Medically unexplained symptoms (MUS) are a considerable presenting problem in general practice. Alexithymia and difficulties with mental elaboration of bodily arousal are hypothesized as a key mechanism in MUS. In turn, this inability influences the embodied being and participating of these patients in the world, which is coined as ‘the lived body’ and underlies what is mostly referred to as body awareness (BA). The present article explores a more innovative hypothesis how hands-on bodywork can influence BA and serve as a rationale for a body integrated psychotherapeutic approach of MUS. Research not only shows that BA is a bottom-up ‘bodily’ affair but is anchored in a interoceptive-insular pathway (IIP) which in turn is deeply connected with autonomic and emotional brain areas as well as verbal and non-verbal memory. Moreover, it is emphasized how skin and myofascial tissues should be seen as an interoceptive generator, if approached in the proper manual way. This article offers supportive evidence explaining why a ‘haptic’ touch activates this IIP, restores the myofascial armoured body, helps patients rebalancing their window of tolerance and facilitates BA by contacting their bodily inner-world. From a trans-disciplinary angle this article reflects on how the integration of bodywork with non-directive verbal guidance can be deeply healing and resourcing for the lived body experience in MUS. In particular for alexithymic patients this approach can be of significance regarding their representational failure of bodily arousal.